Late Triassic porphyries in the Zhongdian arc, eastern Tibet: origin and implications for Cu mineralization. (2nd September 2019) - Dong, Pengsheng; Dong, Guochen; Sun, Zhuanrong; Li, Huawei; Tang, Jiahui; Zhu, Hongyun
Abstract: Whole-rock and Sr–Nd–Pb isotopic composition data, zircon Hf isotopic data and zircon U–Pb ages were obtained for the Late Triassic porphyries in the Zhongdian arc, eastern Tibet. These porphyries are intermediate and metaluminous and are enriched in large ion lithophile elements and depleted in high field strength elements. Moreover, they have weak negative Eu anomalies, high Sr and Ba contents, and high Sr/Y ratios. Different mineral geothermobarometers suggest that the porphyries in the Zhongdian arc crystallized at c . 640–829 °C and pressures of 2.1–2.8 kbar at depths shallower than 8 km. The porphyries have a calculated water content of 4.47–4.94 wt % and a relatively high magmatic oxygen fugacity. These porphyries were emplaced mainly at 230–203 Ma with a peak at 218–215 Ma. The Sr–Nd–Pb–Hf isotope data suggest that the porphyries in the Zhongdian arc were derived from a mixed melt of 50–65 % asthenospheric mantle and 35–50 % eclogite from the western Yangtze lower crust that experienced low-degree partial melting of 2–10 %. Subsequent fractional crystallization resulted in the decreasing trends of the major- and trace-element contents. The high Sr/Y and La/Yb values are the result of the low degree of partial melting of the western Yangtze lower crust rather than fractional crystallization, because no linear relationship was noted between Sr/Y or La/Yb and SiO2 . The mixed melts from the lower crust and asthenospheric mantle provided a fertile magma source, and subsequent fractional crystallization under the favourable magmatic conditions of high water content and high oxidation state resulted in the formation of the porphyry Cu–Au deposits.